4D ultrasound evaluation of fetal facial expressions during the latter stages of the second trimester. Issue 3 (14th March 2013) - Kanenishi, Kenji; Hanaoka, Uiko; Noguchi, Junko; Marumo, Genzo; Hata, Toshiyuki
Abstract: Objective: To assess the frequency of fetal facial expressions at 25–27 weeks of gestation using 4D ultrasound. Methods: Twenty‐four normal fetuses were examined using 4D ultrasound. The face of each fetus was recorded continuously for 15 minutes. The frequencies of tongue expulsion, yawning, sucking, mouthing, blinking, scowling, and smiling were assessed and compared with those observed at 28–34 weeks of gestation in a previous study. Results: Mouthing was the most common facial expression at 25–27 weeks of gestation; the frequency of mouthing was significantly higher than that of the other 6 facial expressions ( P < 0.05). Yawning was significantly more frequent than the other facial expressions, apart from mouthing ( P < 0.05). The frequencies of yawning, smiling, tongue expulsion, sucking, and blinking differed significantly between 25–27 and 28–34 weeks ( P < 0.05). Conclusion: The results indicate that facial expressions can be used as an indicator of normal fetal neurologic development from the second to the third trimester. 4D ultrasound may be a valuable tool for assessing fetal neurobehavioral development during gestation.